A context transfer-based approach to enhance mobility support in multicast - Hassan Abdalla Hashim, Aisha; Nasir Ahmed, Abdi; Mahfouz, Abdulrhman; Khan, Sheroz (CSC Journals, 2008)
With the advent of the handheld devices and multimedia applications, there has been an increasing interest for mobile multicast. IETF proposes two approaches. The first approach is Bi-directional (BT), where the mobile node subscribes to a multicast group through its home network. The second approach is Remote Subscription (RS), where the mobile node joins the multicast group via a local multicast router on the foreign link being visited.